InhA1-Mediated Cleavage of the Metalloprotease NprA Allows Bacillus cereus to Escape From Macrophages - Haydar, Abbass; Tran, Seav-Ly; Guillemet, Elisabeth; Darrigo, Claire; Perchat, Stéphane; Lereclus, Didier; Coquet, Laurent; Jouenne, Thierry; Ramarao, Nalini (Frontiers in Microbiology, 2018)
Bacillus cereus is a Gram-positive spore-forming bacterium causing food poisoning and serious opportunistic infections. These infections are characterized by bacterial accumulation in the host despite the induction of inflammation. To circumvent inflammation, bacteria must resist the bactericidal activity of professional phagocytes, which constitute a first line of host defense against pathogens. Interactions between phagocytic cells and B. cereus are still poorly characterized and the mechanism of resistance to the host immune system is not known yet. We have previously shown that the spores are phagocytosed by macrophages but survive and escape from these cells. The metalloprotease InhA1 is a key effector involved in these processes. inhA1-deficient spores are retained intracellularly, in contrast to the wild type strain spores. NprA is also a B. cereus metalloprotease able to cleave tissue components such as fibronectin, laminin, and collagen. Here, we show that NprA, concomitantly secreted with InhA1 in the B. cereus secretome, is essential to promote bacterial escape from macrophages. We show that InhA1 cleaves NprA at specific sites. This cleavage allows liberation of the mature form of the NprA protein in the supernatant of the wild type strain. This mature form of NprA is actually the principal effector allowing bacterial escape from host macrophages.